Portrayal Of The Iraq War (2005-2008) In The BBC’S English Online News: A Critical Discourse Analysis - al-Shaibani, Ghayth K. Shaker (2010)
This study examined the subsequent events of the Iraq war 2003 by selecting eleven stories from the BBC news website. The corpus covers a span of three years from 15th December 2005 to 1st At the macro level, each text was analysed to assign the global meaning which stands for the Semantic Macrostructure. Whilst, at the micro level, each text was analysed to examine the local meanings in the news discourse in terms of syntactic, lexical, and rhetorical choices. As regards the ideological analysis, it focused on the image of in-group and out-group representations i.e. a positive self-presentation and negative other-presentation at both levels. February 2008 when key events took place in Iraq. The focus of the study was on the macro- and micro-semantics of the texts and ideological representations. To carry out the study, the researcher employed van Dijk’s (1980) theory of Semantic Macrostructure to examine the news discourse at the macro-level and micro-level, and van Dijk’s (1998) theory of ideology to investigate group ideology at both levels.